Students’ Syntax Error in Making English Conversation: An Error Analysis Study - Ida Bagus Gde Nova Winarta; I Wayan Eka Dian Rahmanu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
This Research entitled “Students’ Syntax Error in Making English Conversation, An Error Analysis Study. Basically, it is commonly found that English structure was difficult learned by Indonesian native elementary students. This study was focused on the exploration of foreign language errors and mistakes uttered by younger students. The research method applied in this research consists of approach research, kind and data source, method, and technique of collecting data, method, and technique of analyzing data, and method and technique of presenting the data analysis. A qualitative approach was used in this research and the data source was done by the researcher toward Elementary School 5th Grade Students. The method used in collecting data was by using the observation method and interview method. Then, the result of the analysis was presented by using formal and informal methods. The discussion of the problems was preceded by errors in syntax, such as errors in the scope of clause and phrase, the omission of article and preposition, the omission of the copula be, and error in using to (infinitive). From the result and discussion, it could be concluded that the researcher found some errors in using English done by the Elementary School 5th Grade Students, related to syntax. The writer was aware that this research has some limitations or shortages so it is hoped that this research could be continued in order to get a better result for the society in general.